Pengaruh Transparansi, Akuntabilitas, Dan Partisipasi Masyrakat Terhadap Pengelolaan Alokasi Dana Desa Di Kecamatan Pandaan (Studi Kasus Di Kecamatan Pandaan Kabupaten Pasuruan) - Cindy Sekar Nirwana; Muslimin Muslimin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to examine the effect of transparency, accountability, and community participation on the management of village fund allocations. This study uses a type of quantitative research using primary data. The primary data is in the form of a questionnaire distributed to 84 respondents in villages in Pandaan District, Pasuruan Regency. Selection of the sample in this study using purposive sampling. The results of this study prove that the translation variable has no effect on the management of village fund allocations in Pandaan District. Meanwhile, accountability and community participation have a positive effect on the management of village fund allocations in Pandaan District. Keyword: Transparency, Accountability, Community Participation, Village Fund Allocation Management